Crescimento e qualidade da cebola e efeito residual em alface em função da interação nitrogênio e enxofre - Cipriano, Patriciani Estela (2017)
Adequate amounts of N and S are important to achieve high productivity and also quality products. The objective of this study was to the interaction between N and S in the development of plants of onion (Allium cepa L.) and in post-harvest quality of your bulbs, using the technique of the marked element ( 15 N), as well as the residual effect of nitrogen on nutrition and yield of lettuce (Lactuca sativa L.).The experiment was conducted in a greenhouse, in a completely randomized factorial 3 x 5, with three doses of S (0, 20, 40 mg dm -3 ) and five doses of N (0, 40, 60, 80, 100 mg dm -3 ) with four replications. With the doses of N was applied the 15 N, via the urea checked, which corresponded to 3% of the total N applied. In succession, the onion has been cultivated lettuce, with only the residual effect of nitrogen applied earlier. The variables in the study were: pungency, soluble solids (SS), titratable acidity (TA), , soluble solids / total titratable acidity ratio (SS/TA), fresh bulb mass (FBM), dry bulb mass (DBM), fresh matter loss bulb at 10, 55 and 110 days (FMLB10, FMLB55, F|MLB110), dry mass aerial part (DMAP), total dry mass (TDM), N and S content and accumulation, N/S ratio, N in the plant from the fertilizer (% Ndff), amount of N in the plant from the fertilizer (Adff) and utilization of the N from the fertilizer (% UNff) for the onion culture. For the lettuce crop were evaluated: dry mass aerial part (DMAP), content and accumulation of the macronutrients and N/S ratio. The application of S contributed to reduction of FMLB and increase of FBM and DBM in low doses of N. More pungent bulbs, higher % SS and lower TA were observed with the application of S regardless of the amount of N available. It was found that the application of S increases the production of DMAP independent of the dose of N applied and when in the absence of application of S, the increase in TDM accompanied the increase in the doses of N. At the dose of 100 mg dm -3 of N, the Ndff and UNff variables were not influenced by the application of S with the best use of N from the fertilizer by the onion being obtained with the treatment with 40 mg dm -3 of N and S, with 56.4% under the conditions under which this experiment was carried out. As for the residual effect, the increase in N and S doses showed an increase in N, S and P accumulation and a reduction in K accumulation. The application of S reduced the accumulation of Ca and Mg, but these values increased with the increase in N doses. The combination between the higher doses of N and S applied provided the greater accumulation of DMAP. And the residual effect of the fertilization used for the onion plants did not limit the development of lettuce plants cv. Veronica. The interaction between N and S affected positively, demonstrating that the application of S has a positive effect on the cultures under study.